'Mining' Bitcoin takes more energy than mining gold. (15th November 2018) - Unknown
The cryptocurrency's production generated about as much carbon dioxide over 30 months as 1 million cars in the same period. The cryptocurrency's production generated about as much carbon dioxide over 30 months as 1 million cars in the same period.